2019
DOI: 10.1021/acs.analchem.8b05774
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Measurement of Single Suspended Cells Using a Combined Cell Manipulation System and a Single-Probe Device

Abstract: Existing single cell mass spectrometry (SCMS) sampling platforms are largely designed to work only with immobilized cells and not the suspended cells isolated from patient samples. Here, we present a novel method that integrates a commercially available cell manipulation system commonly used for in vitro fertilization with the Single-probe SCMS sampling technology. The combined Single-probe SCMS/cell manipulating platform is capable of rapidly analyzing intracellular species in real time from a suspension leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 69 publications
2
53
0
Order By: Relevance
“…The need to analyze large numbers of samples in single cell approaches means that robust quality control procedures need to be implemented to ensure that all the generated data is comparable. Although some studies have measured lipids in single cells (Ellis et al, 2012;Neumann et al, 2019;Thiele et al, 2019;Standke et al, 2019) and some have measured in large numbers of cells (Neumann et al, 2019), these approaches have incorporated limited quality control procedures to ensure data consistency across sample sets. In this study we also included a pooled quality control corresponding to unsorted cells, which was added to each plate and enabled us to correct for inter-plate variability (Figure 3).…”
Section: Quality Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to analyze large numbers of samples in single cell approaches means that robust quality control procedures need to be implemented to ensure that all the generated data is comparable. Although some studies have measured lipids in single cells (Ellis et al, 2012;Neumann et al, 2019;Thiele et al, 2019;Standke et al, 2019) and some have measured in large numbers of cells (Neumann et al, 2019), these approaches have incorporated limited quality control procedures to ensure data consistency across sample sets. In this study we also included a pooled quality control corresponding to unsorted cells, which was added to each plate and enabled us to correct for inter-plate variability (Figure 3).…”
Section: Quality Controlmentioning
confidence: 99%
“…However, without imaging all samples lack cell-type specificity and could not guarantee that each sample contained a single cell and not clusters of cells, leading to wide divergence in the number of lipids measured per sample (Neumann et al, 2019). Most single cell mass spectrometry platforms have focused on analyzing immobilized cells; however, Standke et al (2019) developed an integrated cell manipulation platform that enables single cells to be analyzed from solutions, such as bodily fluids, with minimal sample preparation. More complex derivatization approaches have also been described.…”
Section: Introductionmentioning
confidence: 99%
“…In a time when single-cell techniques are blooming in genomics, epigenomics, transcriptomics, and proteomics [64,65], single-cell metabolomics is still in its infancy [66]. Nevertheless, recent studies have demonstrated the feasibility of different techniques for profiling the metabolome at the single-cell level from both cell cultures [67,68] and freshly resected tissues [69]. Among these techniques, mass spectrometry imaging (MSI) spatial metabolomics [70] is perhaps the most widely applicable, with the proven ability to characterize both metabolite levels and isotopic-labeling patterns at subcellular (and even suborganelle) resolutions [71].…”
Section: Box 3 Interpreting In Vivo Tracer Measurements (1): Pathwaymentioning
confidence: 99%
“…The ability to probe cellular heterogeneity may lead to better disease diagnosis, prognosis and treatment [1][2][3][4][5] by enabling the differentiation of subpopulations of disease-causing cells, the discovery of biochemical pathways and mechanisms, and the monitoring of the efficacy of therapeutic intervention. Technologies for performing molecular and chemical analyses at the single-cell level include fluorescence-or mass-spectrometry-based techniques [6][7][8][9][10][11] coupled with flow cytometry, [12][13][14] capillary electrophoresis [15][16][17] or optical microscopy, [18][19][20] in which the biomolecules of interest are labelled. They require complex instruments, centralized laboratory and personnel with expertise, and are often costly and time-consuming.…”
Section: Introductionmentioning
confidence: 99%